The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.2307/40157527
|View full text |Cite
|
Sign up to set email alerts
|

Species Limits and Natural History of Scytalopus tapaculos (Rhinocryptidae), with Descriptions of the Ecuadorian Taxa, including Three New Species

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(103 citation statements)
references
References 11 publications
2
81
0
1
Order By: Relevance
“…Ecuadorian Tapaculos have short, round wings and only limited flight capacities; they do rarely fly distances longer than 3 m and move mainly by walking or hopping (Krabbe and Schulenberg 1997). In this study, we found wing shape to be related to forest size.…”
Section: Morphological Adaptations To Forest Fragmentationmentioning
confidence: 50%
See 3 more Smart Citations
“…Ecuadorian Tapaculos have short, round wings and only limited flight capacities; they do rarely fly distances longer than 3 m and move mainly by walking or hopping (Krabbe and Schulenberg 1997). In this study, we found wing shape to be related to forest size.…”
Section: Morphological Adaptations To Forest Fragmentationmentioning
confidence: 50%
“…The species was only discovered in 1990 (Krabbe and Schulenberg 1997) and is so far not well studied. It occurs in the undergrowth of mature forests and is very reluctant to cross even small areas of open habitat (Krabbe and Schulenberg 1997).…”
Section: Study Species and Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…This is an important biogeographic pattern that was obscured by a mixture of greater and lesser degrees of geographic variation being treated at the same, subspecific level. Many Neotropical bird species comprise well-marked geographical forms, and our understanding of biogeography and diversification processes is likely to be enhanced by careful analyses of that variation, especially when disparate types of data (morphological, behavioral, genetic) are integrated , Bierregaard et al 1997, Krabbe and Schulenberg 1997, Robbins and Stiles 1999.…”
Section: Discussion Species Statusmentioning
confidence: 99%